A Round Trip or «The Myth of No Return» in Eastern European Migration - Romanenko, O. (Народна творчість та етнологія, 2020)
Considering the difficulties of the early 20th-century emigrants’ lives and their controversial fate in their own history of emigration, it is worth saying that they did not always end successfully. The period before, during, and after World War I became particularly active in increasing migration policy for both Americas. The Central and Eastern European regions became labor suppliers primarily to the USA and Canada. The article provides an overview of some cases of unsuccessful emigration to North America and unravels the myth, which from the early 19th century until today has been circulating among emigrants: quick enrichment and a better destiny. The examples cited in the article mainly refer to emigrants from the territory of Galicia (first as a part of the Austro-Hungarian Empire and later as Poland’s lands during the interwar period). Враховуючи труднощі життя емігрантів початку ХХ ст. та їхню суперечливу долю у власній історії еміграції, варто зазначити, що вони не завжди закінчувалися успішно. Період до, під час і після Першої світової війни став особливо активним у посиленні міграційної політики для обох Америк. Регіони Східної і Центральної Європи стали постачальниками робочої сили, насамперед до США та Канади. Стаття показує деякі випадки неуспішної еміграції до Північної Америки та розвінчує міф, що з початку ХІХ ст. і до сьогодні курсує в середовищі емігрантів: швидке збагачення та краща доля. Приклади, що наведені в статті, переважно відносяться до емігрантів з території Галичини (спочатку як складової частини Австро-Угорської імперії, а пізніше польських земель міжвоєнного періоду).